ADSORPSI β-KAROTEN YANG TERKANDUNG DALAM MINYAK KELAPA SAWIT (CRUDE PALM OIL) MENGGUNAKAN KARBON AKTIF - Irvan, Olyvia Putri Wardhani, Nurul Aini, Iriany (Jurnal Teknik Kimia USU, 2016)
Crude palm oil (CPO) is the richest natural source of carotenoids which gives the reddish-orange color in crude palm oil. The reddish color in  unprocessed palm oil is disliked by consumer. This research is aimed to adsorb the β–carotene from the CPO using activated carbon, then the kinetics, isotherm models and thermodynamics data of the adsorption process were obtained. The main materials used in this research were CPO and activated carbon. The observed parameters were final concentration  and the amounts of adsorbed β–carotene in activated carbon. The adsorption process was conducted by mixing the adsorbent with CPO with the variation of adsorbent: CPO (w/w) ratio = 1 : 3; 1 : 4; 1 : 5 and 1 : 6 with mixing  speed 120 rpm and the temperature of 40, 50 and 60 oC. The sample of CPO and activated carbon was analyzed at every 2 minutes until the equilibrium was achieved. The final concentration of the unadsorbed β–carotene was analyzed using UV-Vis spectrophotometer. The results showed that the more CPO used in the process, the lower the adsorption percentage. The higher the adsorption temperature, the higher  adsorption percentage. Moreover, the maximum adsorption percentage was 95.108%  obtained at ratio 1 : 3 and T = 60 oC. The adsorption isotherm model which fit with the β–carotene adsorption at T = 60 oC was Langmuir model with the correlation coefficient of 0.959. The adsorption kinetics model which fit with the β–carotene adsorption was the second order kinetics model with the correlation coefficient of 0.998. The value of free energy Gibbs (ΔG) = -24,482.484 ; -24,708.059 and -24,933.634 J/mol for each temperature respectively, value of entropy changes (ΔS) = 22.557 J/mol K, and value of enthalpy changes (ΔH) = -17,421.987 J/mol.